Physiological Response of Bali Cattle on Anesthetic of Ketamine and Propofol - Pemayun, I Gusti Agung Gde Putra; Sudisma, I Gusti Ngurah (Journal of Veterinary and Animal Sciences; Vol 3 No 1 (2020), 2020)
General anesthesia in Bali cattle using ketamine and propofol has not been reported. Therefore, research is needed to determine the dosage, time of anesthesia and physiological response of ketamine, propofol, and combinations of both (ketafol). Twelve male calves, weighing 25-45 kg with age of 2-4 months were used in this research. Physiological changes in the cardiovascular and respiratory system, also body temperature was monitored using a physiograph tool. All calves were premedicated with xylazine (0.1 mg/kg BW) intramuscularly, and induced with ketamine (2 mg/kg BW), propofol (2 mg/kg BW) and ketafol (1 mg/kg BW ketamine and 1 mg/kg BW propofol) intravenously after 10 minutes. Ketamine induced calves showed results of induction time after 4.75 ± 1.73 minutes, duration of anesthesia is 13.03 ± 1.15 minutes, and recovery time is 12.01 ± 5.05 minutes. The induction time using propofol is 2.50 ± 0.58 minutes, duration of anesthesia is 15.50 ± 1.91 minutes and recovery time is 2.75 ± 0.96 minutes. Calves induced with ketafol produced5.00 ± 1.41 minutes for induction time, duration of anesthesia was 14.00 ± 1.83 minutes, and recovery time was 4.50 ± 0.58 minutes. The calves that were induced with ketamine, propofol, and ketafol show that the induction time and duration of anesthesia are not significantly different, but for propofol’s recovery time was significantly lower compared with ketamine, but not significantly different from ketafol. Anesthesia using propofol or ketafol can be used in Bali cattle because the physiological changes in the cardiovascular and respiratory system are more stable and no extreme changes was found.